Analysis of Gross Regional Domestic Product, Open Unemployment Rate, and Human Development Index on the Percentage of Poor People on the Island of Sumatra in 2013-2022 - Achmad Verdi Jayanto; Neli Aida (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to analyze the effects of Gross Regional Domestic Product (GDP), Open Unemployment Rate (TPT), and Human Development Index (HDI) on the percentage of poor people on the island of Sumatra in 2013-2022. Poverty is a major problem in development, especially in developing countries such as Indonesia. Some of the factors that affect poverty are GDP, TPT, and HDI. This study uses secondary data obtained from related agencies. The analysis method used is multiple regression. The results of the study show that GDP, TPT, and HDI simultaneously have a significant effect on the percentage of poor people on the island of Sumatra. Partially, GDP and HDI have a negative and significant effect, while TPT has a positive and significant effect on the percentage of the poor. The implication of this study is the need for government policies that focus on increasing GDP, decreasing TPT, and increasing HDI to reduce poverty rates on the island of Sumatra.